Systematic Literatur Review: Pengaruh Kinerja Lingkungan terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Variabel Mediasi - Agusalim Agusalim; Imelia Kontesa; Feonagea Feonagea (Journal of Creative Student Research, 2025)
This study aims to examine the influence of environmental performance on firm value, with financial performance serving as a mediating variable, using a Systematic Literature Review (SLR) approach. In recent years, environmental performance has become an essential factor in supporting corporate sustainability, as stakeholders increasingly emphasize environmental issues and corporate social responsibility. The research method involved reviewing relevant national and international scholarly articles published between 2021 and 2025, which were collected through the Google Scholar database.The findings from the literature review indicate that companies with strong environmental performance tend to achieve greater operational efficiency, enhance corporate reputation, and build higher levels of investor trust. These advantages contribute to improved financial performance, particularly in terms of profitability and market performance. Furthermore, better financial performance plays a significant role in increasing firm value in the capital market. The results suggest that financial performance functions as an effective mediating mechanism that strengthens the relationship between environmental performance and firm value. Therefore, effective environmental management should not be viewed solely as regulatory compliance but as a strategic business approach that supports long-term value creation. By integrating environmental considerations into corporate strategy, firms can enhance financial outcomes while simultaneously achieving sustainable growth and competitive advantage.